Deferoxamine reduces amyloid-beta peptides genesis and alleviates neural apoptosis after traumatic brain injury. Issue 6 (11th March 2021) - Zhaba, Wang-Dui; Deji, Qu-Zhen; Gao, Sheng-Qing; Han, Yan-Ling; Gao, Chao-Chao; Deng, Hong-Ji; Liu, Xi-Lin; Li, Tao; Zhou, Meng-Liang
Abstract : Traumatic brain injury (TBI) is recognized as the most influential risk factor for neurodegenerative diseases later in life, including Alzheimer's disease. The aberrant genesis of amyloid-β peptides, which is triggered by TBI, is associated with the development of Alzheimer's disease. Evidence suggests that iron plays a role in both the production of amyloid-β and its neurotoxicity, and iron overload has been noted in the brain after TBI. We therefore investigated the effects of an iron-chelating treatment on amyloid-β genesis in a weight-drop model of TBI in mice. Human brain samples were obtained from patients undergoing surgery for severe brain trauma. The Institute of Cancer Research mice were treated with deferoxamine by intraperitoneal injection after TBI induction. Changes in amyloid-β(1–42) were assessed using western blot and immunohistochemical staining. Ferritin was also detected using western blot to investigate iron deposition in the mice brain. Immunofluorescent terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling was also performed to evaluate neural apoptosis. The amyloid-β(1–42) was markedly elevated after TBI in both humans and mice. Deferoxamine treatment in mice significantly decreased the levels of both amyloid-β(1–42) and ferritin in the brain, and reduced TBI-induced neural cell apoptosis. The iron chelator deferoxamine can alleviate the increase of amyloid-β(1–42) in the brain after TBI, and may therefore be a potential therapeutic strategy to prevent TBI patients from undergoing neurodegenerative processes.